Analysis of strategic planning in startups: exploring practices and the current context of capixaba’s indtechs - Mill, Henrique Caser; Vargas, Lara Gorayeb; Rodrigues, Thiago de Almeida; Oliveira, Rhuan Jadjeschi; Soanno, Jamilly Furtado; Knupp, Thiago Corrêa (Brazilian Journal of Production Engineering, 2024)
The intensification of competition in the business environment has driven startups to formalize their internal practices to expand their market presence. Strategic planning plays a central role in this process. However, the literature lacks studies focusing on the conception and execution of strategic planning in industrial technology startups, also known as indtechs. This study aims to analyze the dynamics of elaborating and implementing strategic planning in these startups, seeking to identify patterns of success and areas for improvement. Thus, a survey was conducted, applying a questionnaire to five managers of indtechs in Espírito Santo. The results mapped relevant aspects of strategic planning in startups, such as the planning elaboration process, plan execution, time horizon, most used tools, internal relevance of planning, and access to external investments, highlighting best practices and challenges. Finally, this study provides for other indtechs to develop their own strategic plans, addressing the specificities of this process in startups, thus enriching the literature on the subject.
Keywords: Strategic planning; Startup indtech; Industrial technology